Membrane-Targeting Neolignan-Antimicrobial Peptide Mimic Conjugates to Combat Methicillin-Resistant Staphylococcus aureus (MRSA) Infections - Yang, Ruige; Hou, Enhua; Cheng, Wanqing; Yan, Xiaoting; Zhang, Tingting; Li, Shihong; Yao, Hong; Liu, Jifeng; Guo, Yong (Journal of medicinal chemistry, 2022)
Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) continue to endanger public health. Here, we report the synthesis of neolignan isomagnolone (I) and its isomer II, and the preparation of a series of novel neolignan-antimicrobial peptide (AMP) mimic conjugates. Notably, conjugates III5 and III15 exhibit potent anti-MRSA activity in vitro and in vivo, comparable to that of vancomycin, a current effective treatment for MRSA. Moreover, III5 and III15 display not only fast-killing kinetics and low resistance frequency but also low toxicity as well as effects on bacterial biofilms. Mechanism studies reveal that III5 and III15 exhibit rapid bactericidal effects through binding to the phosphatidylglycerol (PG) and cardiolipin (CL) of the bacterial membrane, thereby disrupting the cell membranes and allowing increased reactive oxygen species (ROS) as well as protein and DNA leakage. The results indicate that these neolignan-AMP mimic conjugates could be promising antimicrobial candidates for combating MRSA infections.